The Brazilian Society of Mathematical Education and the National Common Curriculum Base (2020)
The Brazilian National Common Curricular Base [NCCB], created between 2015 and 2018, consists of stated curricular documents. Its building process involved strong political aspects and was the center of conflicts and tensions in the educational context of the country. The policy cycle approach, proposed by Ball, has been frequently used by researchers of curriculum policy, among other fields. This approach is a relevant methodological trend for the understanding of curricular reform processes based on the NCCB’s production and influence contexts, on the paradigms that directed the building process, as well as on the ideological tensions resulting from the participation of multilateral organizations. In order to achieve this objective, this article presents an analysis of the positions coming from public documents and interviews with a representative of the Brazilian Society of Mathematical Education, conducted at specific moments during the process of building the document established for learning mathematics in Brazil. The analyses showed a need to reflect on vertical models, silenced voices and mathematical contents as management and performativity instruments printed in the reform.